1991
DOI: 10.1017/s0022336000030341
|View full text |Cite
|
Sign up to set email alerts
|

Stomatopod predation on fossil gastropods from the Plio-Pleistocene of Florida

Abstract: Stomatopods (mantis shrimps) are important predators in Recent tropical shallow-water communities. Despite a long geological history, they are poorly preserved as fossils, and traces of their predation have never been identified from the fossil record. Here we report on Plio-Pleistocene gastropods (mostly Strombus) from Florida with distinctive holes “punched” into their body whorls. The similarity of these holes to holes punched into live gastropods by Gonadactylus implicates gonodactyloid stomatopods as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 10 publications
2
30
0
1
Order By: Relevance
“…Durophagous predators may show a preference for larger (Zach, 1978), intermediate (Geary et al, 1991), or small (Juanes, 1992;Seed and Hughes, 1995) molluscan prey when given a range of potential prey sizes. Because of this selectivity, the frequency of shell repair is expected to increase as shell size increases because the likelihood that a predator will be successful in its attack declines as shell length increases (Vermeij, 1987).…”
Section: Prey Species- Size- and Site-selectivity By Durophagesmentioning
confidence: 99%
“…Durophagous predators may show a preference for larger (Zach, 1978), intermediate (Geary et al, 1991), or small (Juanes, 1992;Seed and Hughes, 1995) molluscan prey when given a range of potential prey sizes. Because of this selectivity, the frequency of shell repair is expected to increase as shell size increases because the likelihood that a predator will be successful in its attack declines as shell length increases (Vermeij, 1987).…”
Section: Prey Species- Size- and Site-selectivity By Durophagesmentioning
confidence: 99%
“…These predators possess powerful raptorial appendages that are used to repeatedly strike, and smash holes in the shells of gastropod prey (Caldwell & Dingle, 1976;Vermeij, 1978;Caldwell, Roderick & Shuster, 1989;Full, Caldwell & Chow, 1989;Geary, Allmon & Reaka-Kulda, 1991;Baluk & Radwanski, 1996). These predators possess powerful raptorial appendages that are used to repeatedly strike, and smash holes in the shells of gastropod prey (Caldwell & Dingle, 1976;Vermeij, 1978;Caldwell, Roderick & Shuster, 1989;Full, Caldwell & Chow, 1989;Geary, Allmon & Reaka-Kulda, 1991;Baluk & Radwanski, 1996).…”
Section: Enemiesmentioning
confidence: 99%
“…These predators possess powerful raptorial appendages that are used to repeatedly strike, and smash holes in the shells of gastropod prey (Caldwell & Dingle, 1976;Vermeij, 1978;Caldwell, Roderick & Shuster, 1989;Full, Caldwell & Chow, 1989;Geary, Allmon & Reaka-Kulda, 1991;Baluk & Radwanski, 1996). Geary et al (1991) reported probable traces of stomatopod predation on gastropods from the Plio-Pleistocene of Florida; they found successful mantis shrimp predation on prey as long as 133 mm (Fasciolaria prey), but the majority of prey were less than 70 mm long. Geary et al (1991) reported probable traces of stomatopod predation on gastropods from the Plio-Pleistocene of Florida; they found successful mantis shrimp predation on prey as long as 133 mm (Fasciolaria prey), but the majority of prey were less than 70 mm long.…”
Section: Enemiesmentioning
confidence: 99%
“…14). Stomatopods have a pair of raptorial appendages, and most have a spiny, spike-like dactylus which they extend forward to stab soft-bodied prey; a few gonodactylid species smash shelled molluscs and crabs with the thickened base or 'elbow' of the folded dactylus (Caldwell &Dingle 1976;Geary et al 1991). The stomatopod dactylus swings forward at an extraordinary velocity of 10 ms-' with ballistic acceleration under water (Burrows 1969), and the prey is either speared or, in the case of gonodactylids, battered repeatedly until shell failure occurs and enough soft tissue is exposed to be extracted with the second, third and fourth maxillipeds.…”
Section: The Predatormentioning
confidence: 99%